2017
DOI: 10.1111/jocn.13494
|View full text |Cite
|
Sign up to set email alerts
|

Women's knowledge and use of prenatal screening tests

Abstract: Perinatal nurses are ideally situated to inform pregnant women about prenatal screening tests to improve access to healthcare services and to ensure informed decisions are made by pregnant women and their partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
1
27
0
1
Order By: Relevance
“…In the current study, 84.1% of the women had received prenatal screening tests. In other studies conducted in Turkey, Seven, Akyuz, Eroglu, Daack‐Hirsch, and Skirton () found that 36.1% of pregnant women had undergone prenatal screening by either the triple or double test, while Öcal et al () observed that 58.1% of pregnant women had undergone one or both tests (Öcal et al, ; Seven et al, ). In Turkey, according to the Ministry of Health Prenatal Care and Management Guideline, all pregnant women should be routinely offered prenatal screening as a part of their prenatal care (Prenatal Care and Management Guideline, ), and indeed, the rate of women who had received prenatal screening tests in our study was high.…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, 84.1% of the women had received prenatal screening tests. In other studies conducted in Turkey, Seven, Akyuz, Eroglu, Daack‐Hirsch, and Skirton () found that 36.1% of pregnant women had undergone prenatal screening by either the triple or double test, while Öcal et al () observed that 58.1% of pregnant women had undergone one or both tests (Öcal et al, ; Seven et al, ). In Turkey, according to the Ministry of Health Prenatal Care and Management Guideline, all pregnant women should be routinely offered prenatal screening as a part of their prenatal care (Prenatal Care and Management Guideline, ), and indeed, the rate of women who had received prenatal screening tests in our study was high.…”
Section: Discussionmentioning
confidence: 98%
“…In general, this referral is made for prenatal diagnostic testing and counseling, but not for prenatal genetic screening. In Turkey, the uptake rate of prenatal screening is around 36% (Seven, Akyuz, Eroglu, Daack‐Hirsch, & Skirton, ). The rates of prenatal screening and diagnostic tests in European countries such as the Netherlands, the United Kingdom, and Denmark are 27%, 61%, and 90%, respectively (Crombag, Bensing, Iedema‐Kuiper, Schielen, & Visser, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the varying health literacy levels and numeracy skills that patients bring to the visit, as well as the personal and value-laden nature of prenatal genetic-testing decisions. [3][4][5][6]7 Other information necessary to convey at this first prenatal visit may include management of preexisting medical conditions, medication use, vaccination, and other emerging concerns for the pregnancy (eg, Zika virus, COVID-19). 8 As a result, the first prenatal visit is unique in that a large volume of information must be effectively conveyed and discussed between the patient and her provider.…”
Section: Introductionmentioning
confidence: 99%